Destruction of Wiślica in 1135 in light of source records and historical literature (part 1: sources) - Krzysztof Benyskiewicz (In Gremium. Studies in History, Culture and Politics, 2020)
Article titled Destruction of Wiślica in 1135 in light of source records and historical literature (part 1. Sources) is the first part of a two-stage cycle dedicated to the presentation of source records and historical research related to the invasion of the city in 1135. The author analyses messages from medieval chronicles and annals, and records the results of archaeological research conducted in the area of Wiślica over several decades. When it comes to narrative sources, the original story about the city's disaster is contained only in the Polish Chronicle by Wincenty Kadłubek. Other chronicles (Dzierzwa's, Greater Poland's, Długosz's) present shortened or extended versions of the original. Therefore, they don't have the values of independent records. The situation of Polish annals looks similar. Valuable content, from a historical point of view, are contained only in the oldest annals, derived from the so-called Annales regni Polonorum deperditi –Annals of the Krakow Chapter and the Short Annals. The late fourteenth-to-fifteenth century annals provide information that is the effect of the authors' conjectures.Most probably, the lost old annals were also the basis of the story by Wincenty Kadłubek. The chronicler, known for showing off rhetorically, extended the one-page message from the annals into an extensive (3 chapters of the third book of the chronicles) narrative about the destruction of Wiślica by the son of the Russian prince Volodar. According to the author of the article, the colourful tale of revenge, betrayal, bloody slaughter and punishment for infidelity is the product of the chronicler's imagination. The plot of the account was based on themes drawn, above all, from the biography of Piotr Włostowic. In this situation, Kadłubek's account can't be the foundation for the reconstruction of events in Wiślica in 1135.The basis of knowledge about the city's fate will remain mentions in the oldest annals, supplemented by the results of archaeological explorations. The results of the search so far, abounding in interesting finds require, however, a thorough study. A modest message from annals can get significant support, after reconciling, among others, chronology of relics of buildings and artefacts discovered in Wiślica and surrounding areas.